10.1016/s1541-9800(05)70709-2 (CrossRef Listing of Deleted DOIs, 2000)
Background The emergency department is a challenging environment in which to implement and sustain change, due to unpredictable workloads, the undifferentiated nature of patient presentations and high staff turnover. Synthesising factors that impact practice change in the emergency department is needed to support evidence-based practice. Objective To identify, examine and synthesise barriers and enablers to clinician behaviour change for implementation of patient interventions in the emergency department. Information sources Medical Literature Analysis and Retrieval System Online (MEDLINE), Cumulative Index of Nursing and Allied Health Literature (CINAHL), Embase and Scopus, 2010-2024. Methods This registered systematic review included primary qualitative, quantitative and mixed-methods research reporting on barriers and/or enablers to emergency department interventions. Quality of evidence was assessed using the Mixed Method Assessment Tool with no studies excluded. A convergent-integrated approach to data-based synthesis was conducted. This involved quantising (transforming) qualitative data. Results Of 7128 records yielded, 73 met inclusion criteria. Qualitative (56.1%), quantitative (21.9%) and mixed methods approaches (21.9%) were represented, including interviews, focus groups, surveys and observational studies. The most common barriers were staff time constraints/workload, lack of resources impacting abilities to implement and clinician perceptions about the usefulness of the intervention or their roles. Enablers were organisational culture amenable to change and beneficial interventions for patients and staff. Frameworks were used in only half of the included studies, and those that did were clearer in their description of barriers or enablers. Conclusions Many factors impact successful implementation in the emergency department setting. Clinicians, policy makers and researchers need to understand and learn to address barriers and enablers to achieve successful practice change. More research is needed to find effective strategies to reduce barriers and boost enablers, especially at rural sites. Implications for the profession and/or patient care Emergency departments are under pressure to maintain currency of evidence, requiring rapid translation. Understanding barriers to implementation can support quick and effective implementation of new evidence into practice, leading to improved patient outcomes and reduced change fatigue for staff. Impact Implementation of evidence-based practice can be difficult in complex environments like the emergency department. Synthesis of current evidence identified barriers and enablers to implementation in emergency departments to inform policy and future change planning by clinicians, policy makers, researchers and implementors. Reporting method This registered systematic review followed the Preferred Reporting Items for Systematic Reviews (PRISMA). Patient or public contribution This study did not include patient or public involvement in its design, conduct or reporting. This was a systematic review of the literature specific to staff behaviour change. Protocol registration PROSPERO CRD42022374943, registered 11/2022.